Strategy of Spreading Aswaja Understanding by Nurul Furqon Boarding School Tomia Wakatobi, Southeast Sulawesi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
As a country rich in diversity, Indonesia has witnessed a red ink history of religion-related violence. In Southeast Sulawesi, the majority Muslim population lives a peaceful religious life. However, potential conflicts arise on the basis of ethnicity, not religion. Although violence in the name of religion has not yet occurred, radical and intolerant movements are growing, demanding in-depth understanding and effective preventive measures. this research aims to Know the strategy of Pondok pesantren nurul furqon in spreading aswaja understanding. The place of research conducted at the nurul furqon boarding school in Tomia Wakatobi, Southeast Sulawesi. Research conducted by researchers includes descriptive qualitative research with the type of case study. Data collection techniques include observation, interviews and documentation. The data analysis model includes data reduction, data presentation, and conclusion drawing. The results of this study show that Pondok Pesantren Nurul Furqon has successfully implemented a stunning strategy, involving elements such as Hadrah, majlis ta'lim, and the leadership role of the kiyai as key elements in the spread of Aswaja. More than just an educational institution, this study highlights the central role of pesantren in maintaining the sustainability of Aswaja values, while guarding against potential radicalism.